Cervical lymph node metastases from remote primary tumor sites. (29th December 2015) - López, Fernando; Rodrigo, Juan P.; Silver, Carl E.; Haigentz, Missak; Bishop, Justin A.; Strojan, Primož; Hartl, Dana M.; Bradley, Patrick J.; Mendenhall, William M.; Suárez, Carlos; Takes, Robert P.; Hamoir, Marc; et al.
Abstract: Although most malignant lymphadenopathy in the neck represent lymphomas or metastases from head and neck primary tumors, occasionally, metastatic disease from remote, usually infraclavicular, sites presents as cervical lymphadenopathy with or without an obvious primary tumor. In general, these tumors metastasize to supraclavicular lymph nodes, but occasionally may present at an isolated higher neck level. A search for the primary tumor includes information gained by histology, immunohistochemistry, and evaluation of molecular markers that may be unique to the primary tumor site. In addition, 18F‐fluoro‐2‐deoxyglocose positron emission tomography combined with CT (FDG‐PET/CT) has greatly improved the ability to detect the location of an unknown primary tumor, particularly when in a remote location. Although cervical metastatic disease from a remote primary site is often incurable, there are situations in which meaningful survival can be achieved with appropriate local treatment. Management is quite complex and requires a truly multidisciplinary approach. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E2374–E2385, 2016